Staphylococcus aureus: prevalence and shifting antibiotic landscape in clinical samples from a tertiary care hospital - Anand, Surabbhi; Panda, Pragyan Swagatika; Joe Thomas, Bonnie; Vats, Kanak; Haider, Mehvash; Rynga, Dabet (International Journal Of Community Medicine And Public Health, 2025)
Background: Staphylococcus aureus is a versatile pathogen causing myriads of detrimental infections in both hospital-acquired and community-acquired settings with its notorious ability to develop antimicrobial resistance (AMR). As the world is battling the persistent rise in antimicrobial resistance (AMR), MRSA (Methicillin-resistant Staphylococcus aureus) is a major concern. Adequate data and information about evolving landscape of antibiotic resistance in S. aureus is essential for effective interventions to contain the global crisis of AMR. Methods: A total of 1545 isolates of S. aureus from various clinical samples received from January 01, 2023 to December 31, 2023 in a tertiary care hospital were screened for their antibiotic susceptibility pattern (AST). AST was performed by Kirby Bauer Disc diffusion and MIC determination by VITEK 2 AST system and interpretation done as per CLSI M100-S33, 2023 guidelines. Results: Out of 30,000 clinical samples received and 21% culture positives, S. aureus was found in 5.15% (1545) of cases with 62% being MRSA. A predominance in 20-30 years with female preponderance seen. Cotrimoxazole (82%) was the most effective antibiotic, followed by gentamicin (78%) and clindamicin (71%). While penicillin resistance stood at 96%, and ciprofloxacin reached 91%. Conclusions: A constant shift is resistance pattern with rising prevalence of MRSA isolates, makes it imperative to customize the treatment protocols as per the healthcare specific antibiogram. Continual screening for S. aureus infections and analysing its antibiotic profile is mandatory to update clinicians on effective clinical management, preventing prolonged hospitalization, compromised patient outcomes, and increased burden on healthcare expenses.